Effect of the ambient conditions on gas turbine combined cycle power plants with post-combustion CO2 capture. (1st September 2017) - González-Díaz, Abigail; Alcaráz-Calderón, Agustín M.; González-Díaz, Maria Ortencia; Méndez-Aranda, Ángel; Lucquiaud, Mathieu; González-Santaló, Jose Miguel
Abstract: This paper evaluates the effect of ambient conditions on a natural gas combined cycle power plant (NGCC) with CO2 capture and proposes design options for effective integration and off-design operation. In particular, the study assesses the effect of ambient temperature in the context of the electricity system in Mexico and proposes supplementary firing in the heat recovery steam generator to mitigate reduction in power output. For ambient temperature varying from −5 °C to 45 °C, a typical temperature variation in the north of Mexico, the efficiency of the NGCC with CO2 capture reduces from 50.95% to 48.01% when the temperature increased from 15 °C (ISO design condition) to 45 °C, and reduces from 50.95% to 50.78% when the temperature decreased from 15 °C to −5 °C. The power generated decreases from 676.3 MW at 15 °C to 530 MW at 45 °C. In order to compensate for the loss of output caused by seasonal changes in ambient temperature, supplementary firing in the heat recovery steam generator can be used to generate additional power and return the power output to 640 MW at 45 °C, at the expense of an increase in fuel costs and a drop in efficiency from 50.95% to 43.46%, without and with supplementary firing respectively. Highlights: Ambient temperature is affects the power generating and the efficiency of power plant. The ambient temperature has an impact on the levelised cost of electricity. The design of power plant requires flexibility to operate with and without capture. LP steam turbine capable to operate with capture off line but condenser with capture.